The Influence of Numerical Ability and Abstract Thinking on Mathematical Problem Solving - Ulfa Sari Kumala Dewi; Suaedi Suaedi; Muhammad Ilyas (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2022)
Abstract:This research is ex post facto that aims to examine the influence of numerical ability and abstract thinking on mathematical problem-solving skills of eighth-grade students of SMP in Palopo. The population of this research is the student's class VIII students in Palopo, totalling 212 students, but the sample is 70 students have amounted to 10 students from each class. The selection of the samples used was a proportional random sampling technique. The research instrument used is the numerical ability test, abstract thinking test, and mathematics problem-solving test. The data was obtained by statistical analysis of descriptive and inferential statistics. The result of this research is an influence of numerical ability and abstract thinking on the mathematics problem-solving ability of eighth-grade students of SMP in Palopo. Numerical knowledge and abstract thinking have a contribution effect of 44.1% on students' mathematics problem-solving abilities.Abstrak:Penelitian ex post facto ini bertujuan mengkaji pengaruh kemampuan numerik dan berpikir abstrak terhadap kemampuan pemecahan masalah matematika siswa kelas VIII di salah satu SMP di Palopo. Populasi dalam penelitian ini adalah siswa SMP kelas VIII yang berjumlah 212 siswa, terbagi dalam 7 kelas. Sampel penelitian berjumlah 70 siswa yang dipilih dari 10 orang dari masing-masing kelas secara proporsional random sampling. Instrumen penelitian yang digunakan adalah tes kemampuan numerik, tes berpikir abstrak dan tes pemecahan masalah matematika. Data yang diperoleh dianalisis dengan analisis statistika deskriptif dan statistika inferensial. Hasil penelitian menunjukkan terdapat pengaruh kemampuan numerik dan berpikir abstrak terhadap kemampuan pemecahan masalah matematika siswa kelas VIII di salah satu SMP di Kota Palopo. Kemampuan numerik dan berpikir abstrak memiliki pengaruh kontribusi sebesar 44,1% terhadap kemampuan pemecahan masalah matematika siswa.